2019
DOI: 10.1515/iwp-2019-2006
|View full text |Cite
|
Sign up to set email alerts
|

Retractions from altmetric and bibliometric perspectives

Abstract: Information. Wissenschaft & Praxis 2019; 70(2-3): 98-110 aléatoire. Un modèle de régression binomial permet d'estimer la probabilité qu'une publication soit retirée pour cause d'inconduite ou d'erreurs. Dans l'échantillon de scores altmétriques élevés, nous avons trouvé une corrélation positive entre les « Altmetric attention Scores » et la probabilité de retrait pour cause d'inconduite ou d'erreurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Regardless of this, Furman, Jensen, and Murray (2012) observed that biomedicine retractions cause an immediate, severe, and long-lived decline in future citations to their authors. Shema, Hahn, Mazarakis, and Peters (2019) compared the altmetrics impact of retracted papers, noticing a significant social media impact for these publications. However, retractions are not uniformed by disciplines or regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regardless of this, Furman, Jensen, and Murray (2012) observed that biomedicine retractions cause an immediate, severe, and long-lived decline in future citations to their authors. Shema, Hahn, Mazarakis, and Peters (2019) compared the altmetrics impact of retracted papers, noticing a significant social media impact for these publications. However, retractions are not uniformed by disciplines or regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The presence of extra-topical factors also influence the amount of Twitter attention an article receives. Prior research has found that retractions based on research misconduct attract substantially more online attention than retractions due to error, while the opposite is true of post-retraction journal citations [30,31]. However, neither study performed user or content analysis of the tweets.…”
Section: Characteristics Of Online Attention To Retractionsmentioning
confidence: 95%
“…These full deletions could cause erroneous assumptions drawn from statistics and imply an instability of Wikipedia references as a measurement instrument. In classical bibliometric approaches, comparable issues are negligible since changes of the reference lists in papers are almost impossible, and retractions of papers (together with their referencing lists) are very rare events (Shema et al, 2019). But for altmetrics, the phenomena of citation data volatility need to be discussed in the community.…”
Section: Evolution Of Wikipedia Referencesmentioning
confidence: 99%